Eksistensi Akad Dalam Bingkai Transaksi Bisnis Modern :Transaksi Bai’mu’athah di Supermarket - Indrawati, Titis; Hanifuddin, Iza (Invest Journal of Sharia & Economic Law, 2021)
This study aims to find out how the existence of contracts in the frame of everyday business transactions, especially in bai'mu'athah transactions that occur in supermarkets. This study uses a qualitative research method with a library research approach. It is called library research because the data or materials needed to complete it comes from books and journals. The data collection method is the descriptive analysis method. Moreover, the analysis technique used is content analysis. The findings of this study are that in business transactions, contracts have an essential meaning in people's lives and are the basis of many human activities. The Islamic view of the contract has no limits as long as it is by the terms and pillars of the contract. However, along with the development of modern times to facilitate transactions and flexibility, the contract can be made directly, without using words, writing, or expressing the will. However, it is carried out with the actions of both parties that reflect their willingness and agreement, which is commonly known as a bai'mu'athah transaction. These transactions are found in supermarkets, where supermarkets use electronic barcode media that machines can only read. Bai'mu'athah transactions do not meet the requirements and pillars of the contract, but according to Maliki in the most rajih qaul, the law of buying and selling mu'athah is valid if it has become a daily habit that shows willingness, and the act describes the perfection of each other's desires. Each party. Moreover, some Shafi'i scholars allow bai'mu'athah transactions